Below the standard market: A study of dispersed rural settlement patterns on the Chengdu Plain and Skinner's theory on marketing hierarchy. Issue 4 (2nd October 2018) - Shang, Yuan
Abstract: Under G. William Skinner's theory on marketing hierarchy, "minor markets" (小市 xiaoshi ) (or 么店 yao dian, "general store"), ranking below a "standard market, " were closely tied to rural settlement patterns. Natural conditions on the Chengdu Plain, farmers' pursuit of convenience in farm work, and the history of the arrival and settling of immigrants to Sichuan in the early Qing dynasty combined to shape the foundation for the landscape of dispersed settlement observed by Skinner during his field study. These settlement patterns reflected not only a state of spatial dispersal, but also a relatively isolated social structure. On both a spatial and societal level, "marketing" therefore had an important integrating significance for society and the economy on the Chengdu Plain, and Skinner's theory on marketing hierarchy is furthermore in accord with the reality of the Chengdu Plain.